ANALISIS EMPIRIS PERGANTIAN KANTOR AKUNTAN PUBLIK SETELAH ADA KEWAJIBAN ROTASI AUDIT (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI periode 2009-2011) (Students' Journal of Accounting and Banking, 2014)
The purpose of this study was to examine institutional ownership , public ownership, boards of commissioners, share growth, replacement of the board of directors, leverage, ROE and firm size may affect the auditor's reputation companies listed in Indonesia Stock Exchange ( IDX ) in the turn of a public accounting firm.The sample in this study is a manufacturing company that is listed on the Indonesia Stock Exchange from 2009-2011. Methods of data collection in this study was purposive sampling method, which is based on specified criteria. Based on purposive sampling method, the total sample was 22 companies. This hypothesis was tested using logistic regression analysi.,The results show that Public ownership, board of commissioners, share growth, replacement of the board of directors, leverage, ROE size and reputation of the company auditor does not significantly influence the turn of the Public Accounting Firm (KAP).Keywords : institutional ownership, public ownership, boards of commissioners, share growth, replacement of the board of directors, leverage, ROE, firm size and auditor reputation